Geographical and Epidemiological Characteristics of Sporadic Coronavirus Disease 2019 Outbreaks From June to December 2020 in China: An Overview of Environment-To-Human Transmission Events - Feng, Maohui; Ling, Qiong; Xiong, Jun; Manyande, Anne; Xu, Weiguo; Xiang, Boqi (Frontiers in Medicine, 2021)
China quickly brought the severe acute respiratory syndrome coronavirus 2 under control during the early stage of 2020; thus, this generated sufficient confidence among the public, which enabled them to respond to several sporadic coronavirus disease 2019 outbreaks. This article presents geographical and epidemiological characteristics of several sporadic coronavirus disease 2019 outbreaks from June to December 2020 in China. The data show that the coronavirus disease may be transmitted by imported cold-chain food and international exchange, and this viewpoint deserves our great attention.